Environmental Crisis and Legitimacy Struggle: A Discourse Network Analysis in the Prabumulih Oil Spill Case - Karter, Tasya Febi; Santoso, Anang Dwi; Saraswati, Erlisa (JURNAL KOMUNIKASI INDONESIA, 2023)
This study seeks to comprehend the legitimacy dynamics of various actors involved in the oil pipeline spill case in Sungai Kelekar, Prabumulih City. A dataset consisting of 132 online media articles curated into 36 pertinent news stories was analyzed using the discourse network analysis method. The results of this study indicate that the community plays a crucial role as mediators and victims, which are the primary criteria for evaluating the moral legitimacy of those who pollute the environment and local governments, where it was also discovered that the two organizations in this study face a variety of challenges in maintaining their legitimacy. This study's implication is serious efforts are required to enhance environmental governance and public participation. This study aims to contribute to the literature on legitimacy management in contentious environmental cases and provide a method for measuring and comprehending the complexity of stakeholder interactions.